Organoleptic Analysis, Quality Requirement, And Color Determination of Tilapia Nuggets with Eleutherine palmifolia Extract Coating - Anggarkasih, Made Gayatri; Febrinda, Andi Early; Adzkiya, M Agung Zaim; Khasanah, Khaula Azizah Nur; Rahman, Rama Salsabila; Maulani, Siti Patimah Zahro (Green Engineering Society, 2023)
Nuggets are a product that should be stored frozen, but nuggets are often sold at inappropriate temperatures, causing physical changes such as pale color. Dayak onion extract can improve color appearance and provide added antioxidant value to tilapia nuggets. Quality testing of tilapia nuggets with Eleutherine palmifolia (Dayak onion) extract coatings has been investigated. The objectives of this research are to apply Dayak onion extract to improve the appearance of tilapia nuggets and to obtain tilapia nuggets with Dayak onion extract that meets SNI requirements. The results of organoleptic tests showed that panelists preferred tilapia nuggets with Dayak onion extract over commercial controls and nuggets. The panelists preferred tilapia nuggets with 100 ppm ethanol extract and 10000 ppm aqueous extract, both continued to the SNI conformity test. The sensory evaluation results based on SNI showed that the appearance of the tilapia nuggets with 100 ppm ethanol extract was significantly different. Adding Dayak onion extract to tilapia nuggets affected the lightness and yellowness of tilapia nuggets and gave a 'moderate orange' color to the tilapia nuggets with ethanol and aqueous extract. The selected tilapia nugget with 100 ppm aqueous Dayak onion extract meets all chemical, microbiological, and sensory requirements as SNI 7758:2013 concerning fish nuggets. Tilapia nuggets with Dayak onion extract had a brighter Moderate orange color and were preferred by panelists compared to controls and commercial fish nuggets that were moderate dark orange. Applying Dayak onion extract on tilapia nuggets can improve the appearance and it potentially contains natural antioxidants.